Study on ionic conduction of alginate bio-based polymer electrolytes by incorporating ionic liquid - Ahmad Faizrin, Fuzlin; Izan Izwan, Misnon; Nagao, Yuki; Ahmad Salihin, Samsudin (Elsevier Ltd, 2021)
Biopolymer electrolytes is attracting a great deal of interest as a substitute for synthetic polymer electrolytes in electrochemical devices. They are carbon–neutral, sustainable, and reduce dependency on non-renewable fossil fuels, and easily biodegradable. The present work aims to develop the alginate bio-based polymer electrolytes (BBPEs) with the addition of various composition (2 to 10 wt%) of ionic liquid (1-butyl-3-methylimidazolium chloride) via solution casting technique. The ionic conduction study was characterized using electrical impedance spectroscopy (EIS) at different frequencies ranging from 50 Hz to 1 MHz. With the addition of 6 wt% 1-butyl-3-methylimidazolium chloride ([Bmim]Cl), the ionic conductivity of the BBPEs system was improved significantly from 5.32 X 10-5 S cm-1 to 2.03 X 10-3 S cm-1 at ambient temperature. The electrical properties analysis revealed that the ionic conductivity sample-based BBPEs has a good relationship with electrical properties formulism and shows non-Debye behavior where no single relaxation occurred in the present system.